Analgesic and anthelmintic activities in common fruits of the Sundarbans mangrove forest, Bangladesh (Bangladesh Journal of Botany, 2023)
The analgesic and anthelmintic activities of the common fruits in the Sundarbans forest, Bangladesh were evaluated. Acetic acid-induced writhing test and hot plate test in mice model were demonstrated for examining the analgesic activity whereas an anthelmintic test was performed using a flatworm, Paramphistomum cervi of livestock ruminants. Among the fruits, Ceriops decandra showed the strongest analgesic activity through inhibiting acetic acid-induced writhing (45%) and increasing response time (16.8 sec) on a hot plate in mice at 250 mg extract/kg body weight (b.w.). Diclofenac sodium (25 mg/kg b.w.), a positive control, demonstrated writhing inhibition of 51.3% whereas morphine (10 mg/kg b.w.), a wellknown centrally active analgesic drug, increased response time of 18.2 sec. The fruits showed inhibition of acetic acid-induced writhing in mice with strong correlations to both the total polyphenols (r2 = 0.85) and the total flavonoids (r2 = 0.81) contents. Similar results were also observed for an increase of response time in mice on hot plate test. Therefore, both the peripheral and the central analgesic activities of the fruits were profoundly related to their total contents of polyphenols as well as flavonoids. Extract of Aegiceras corniculatum fruit displayed the strongest anthelmintic activity with the lowest CDT50 (concentration for death time 50) of 0.69 mg extract/ml whereas albendazole, a positive control, had CDT50 of 5.60 mg/ml for the parasite. The anthelmintic activity of the fruits was not dependent on their contents of polyphenols (r2 = 0.30) or flavonoids. The chromatograms of HPLC-DAD analysis detected caffeic acid, (+)-catechin hydrate, p-coumaric acid, (-)-epicatechin, rutin hydrate, and syringic acid in C. decandra fruit extract and quantified as 10.6, 598.4, 1.5, 28.5, 2 and 1.3 mg/100 g extract, respectively. Results revealed that C. decandra and A. corniculatum fruits are the potentials to treat pain and helminthiasis, respectively.Bangladesh J. Bot. 52(1): 79-86, 2023 (March)